Usage of 3D body scanning technology in judo - Simenko, J. (1st scientific and professional conference on judo "Applicable research in judo" - Book of abstracts, 2015)
With the progress oftechnology andapplication of 3D body scanner methods of measuring body segments, measures have become contactless, fast and above allaccurate (Simmons, &Istook, 2003; Zhangetal., 2014).The aim of this study is to present the method and technology of 3D body scanning and its usefulness for judo.